A brief primer on the mediational role of BDNF in the exercise‐memory link - Loprinzi, Paul D.; Frith, Emily (Clinical physiology and functional imaging, 2019)
Summary One of the most amazing aspects of the human brain is its ability to learn information and use it to change behaviour. A key neurotrophin that influences memory function is brain‐derived neurotrophic factor (BDNF). This review briefly discusses the mechanistic role that BDNF may play in facilitating learning and memory. We also describe the role of exercise on this relationship. As discussed herein, BDNF may influence memory via BDNF‐induced alterations in membrane receptor expression and translocation, as well as activating several pathways (PLC‐y, PI3K, ERK) that act together to facilitate cellular effects that influence synaptic plasticity. Exercise may help to facilitate BDNF expression and its downstream cellular pathways from both direct and indirect mechanisms.